SOSIALISASI SOSIALISASI DAN PENGENALAN PEMBALUT WANITA BERKUALITAS SEBAGAI UPAYA PENCEGAHAN KANKER SERVIKS - Kristina Moinono Nono; Maria T. Danong; Maria T.L Ruma; Fransiskus Kian Duan; Theresia L. Boro (Jurnal Pengabdian Kepada Masyarakat, 2026)
Abstract Women's reproductive health is one of the important indicators in public health development. One disease that still poses a serious threat to women is Cervical Cancer. This disease is generally caused by Human Papillomavirus (HPV) infection, but other risk factors such as low awareness of reproductive organ hygiene also play a role in increasing vulnerability to this disease. In addition, low awareness of reproductive organ hygiene, the use of feminine products that do not meet health standards, as well as lack of education about proper menstrual hygiene practices. One aspect that is often overlooked is the selection of safe and quality sanitary pads. This community service activity aims to increase the knowledge and awareness of women in the Ekam area, Kotabes Village, regarding the importance of recognizing quality sanitary pads as an effort to prevent reproductive health disorders, including cervical cancer. The methods used include counseling, product demonstrations, and evaluations. The material provided includes an introduction to cervical cancer, the importance of maintaining reproductive organ hygiene, characteristics of quality sanitary pads, and the correct way to use sanitary pads. The results of the activity showed an increase in participants' knowledge after attending the socialization, indicated by the difference in scores between the pre-test and post-test. In addition, participants also showed a more positive attitude toward the importance of maintaining hygiene during menstruation and became more selective in choosing sanitary pad products. Keywords: cancer, cervix, quality, sanitary pad, women, menstruation, reproduction, socialization, Kotabes